Non-performing loans (NPLs) determination of commercial banks - ZAHIDOGLI, Ahmad Jawed (KDI School, 2023)
Significant role of banking institutions on economic development of the countries have been drawn the interest of policy makers, academicians, administrative holders and finance professionals to look at this sector more critically and provide deep analysis to avoid any further failures. Therefore, this study tries to examine the factors which affects Non-Performing Loans (NPLs) in the banking sector of Afghanistan by using panel data for the period of 9 years (from 2010 to 2018). Considering the nature of data, fixed and random effect model was utilized and after performance of Hausman test, fixed effect was elected as best model of estimation for this study. For this study, percentage of non-Performing loan over the total loan was used as dependent variable and GDP, annual percentage of economic growth, Inflation, annual changes in inflation rate, CAR, capital adequacy ratio of commercial banks which is measured by dividing shareholders equity to total asset, LR, liquidity ratio measured by dividing total loan to total deposit and size of the bank (Log total asset) were chosen as explanatory variable. The result of the study shows that NPLs level of commercial banks in Afghanistan was sensitive to both macroeconomic and bank specific determinants. In particular, inflation as macroeconomic and capital adequacy ratio as bank specific variables had significantly negative effects on NPLs level of banking industry in the country. The policy implication of the result recommends that policy makers and supervisory as well as management bord of commercial banks are required to monitor, evaluate and predict the inflation level in Afghanistan while approving credits to the customers. Further, the result implies that the regulators at central bank of Afghanistan needs to implement Basel accords fully with within a specific time farmwork in order to avoid adverse effect of credit risk on the industry.
Thesis(Master) -- KDI School: Master of Public Policy, 2023
Keywords: Bank loans--Afghanistan; Debt--Afghanistan